Estrategias de gestión del patrimonio intangible para revalorizar la cultura montubia en Manabí - García Pin, Yandry José (2022)
The objective of this study was to structure strategies for the revaluation of the montubia culture in Manabí, this research is of an exploratory and descriptive nature. In the first phase, the Manabí territory was characterized under a comprehensive analysis of the cantons with great cultural and heritage value; as a second phase, the management of intangible cultural heritage was evaluated. In the third phase, management strategies framed in the reality of intangible assets in Manabí were structured, determining that 34 intangible cultural assets are registered in Manabí, which are located largely in rural areas; the devaluation of the heritage is evident, and the competent organisms do not use measures for its conservation. The evaluation of the management of intangible assets allowed us to know that there are few links between the private company and the provincial government for their conservation, which shows the weak proposal to promote traditional ancestral practices; finally, 9 experts were taken into consideration who approved the criteria related to traditions and intangible cultural heritage, these actions are linked to planning, management and conservation, based on this a program was developed that links collaboration with communities and their respective cultural organizations, formal and informal. Finally, a proposal was presented based on strategies consistent with the management of intangible cultural heritage, in order to revalue Montubio culture through workshops on oral traditions, recovery of ancestral gastronomy and ancestral medicine, to strengthen intangible cultural heritage.